Hubungan Senam Zumba Dengan Indeks Massa Tubuh - Fitriana, Laela Nur; , Totok Budi Santoso, S.Fis., S.Pd., M.Ph (2016)
Background: Weight mainly illustrate the imbalance of energy intake and used in the body that occur in a long term. To determine whether a person is overweight need an objective assessment by using body mass index. Body mass index (BMI) is an objective instrument used to measure the relationship of height and weight of individuals to diagnose the health risks. The important intervension for preventing and managing overweight is by doing physical activity. The gymnastics of zumba dance is a new kinds of exercise inspired by music and dance of Latin America. Zumba exercise combines the basic dance of meringue, salsa, samba, cumbia, reggeaton and other Latin American dances, using the basic step of aerobics, and also composed of other dances such as hip-hop, belly dance, Indian, African dance. Objective: To determine the relationship of zumba exercise on body mass index (BMI). Methods: This study applied observation method with cross sectional approach. The sampling technique was done by using purposive sampling, 90 respondents were included in this study, the respondents who did zumba gymnastics were 45 respondents and who did not do zumba gymnastics were 45. The data were then analyzed by using statistical test of chi square test with significance level <0.05. Results: Based on the chi-square test of the relationship of zumba exercise on body mass index showed p-value of 0.507 or (signifikasnsi) > 0.05 and the statistical test of zumba exercise zumba on body mass index showed p-value 0.667 or significance of > 0.05. Conclusion: There is no relationship of zumba exercise on body mass index